Asymptomatic Presacral Paraganglioma: Management of an Unpredictable Intraoperative Finding - Samara, Athina A.; Diamantis, Alexandros; Symeonidis, Dimitrios; Anagnostou, Athanasios; Diamantis, Andreas Marios; Mavrovounis, Georgios; Tepetes, Konstantinos (The Surgery Journal, 2020)
Paragangliomas are rare neuroendocrine tumors originating from the embryological neural crest. We report a rare case of a patient with an asymptomatic presacral mass (incidentaloma) who experienced an unpredictable intraoperative hypertensive crisis after manipulation of the tumor. Presacral neoplasms pose a diagnostic and therapeutic challenge due to their obscure anatomical location and the difficulty in performing an R0 excision. Furthermore, the management of asymptomatic paragangliomas requires a high level of clinical suspicion and expertise due to potential life-threatening intraoperative complications.
Keywords: paraganglioma; secreting tumor; presacral paragangliomas; 131-I MIBG; neoplasm